Aflatoxin contamination of various raw foods arises when a toxin-producing strain, Aspergillus flavus, grows on substrates in areas where suitable environmental conditions are present for the development of the mould. The mould develops on substrates high - JAFFAR, M.; SALEEM, M.; SALEEM , NAJEEBA; AHMED , MAQSOOD (Biological Sciences - PJSIR, 2022)
samples were stored in high density polythene bags at -20°C until analysed. The Romer method [7,8] was followed for the quantification [8]. Relevant details of the procedure are gi ven in our earlier work [6]. Recovery of the aflatoxin by the standard addition method ranged between 97-101 %. Each estimation was performed in triplicate. Aflatoxin reference standards were obtained from Rijiks institute vwr volkgezondeheit, Bilthoven, Netherland.